FRI0577 Clinical characteristics of spontaneus fractures in the bedridden patients unintentionally caused by caregivers. (15th June 2017) - Kashiwagura, T; Kimura, Y; Wakabayashi, I; Fujii, M; Nozaka, K; Miyakoshi, N; Shimada, Y
Abstract : Background: The number of bedridden patients in our super-aging society is increasing. We previously studied fractures occurring in bedridden patients during daily activities with caregiver assistance (dry baths, range of motion exercises, transfer to wheelchair, changing diapers, and so forth) and non-traumatic fractures detected by pain, swelling, subcutaneous bleeding, deformity, and so on. These minimal trauma or spontaneous fractures were defined as " spontaneus fractures in the bedridden patients unintentionally caused by caregivers ". Despite efforts to draw attention to preventing these injuries, the incidence of such fractures has been increasing. Spontaneus fractures caused by caregivers are characterized by the presence of untreated osteoporosis, contracture or spasticity near the lesion, institutionalization or hospitalization, repeated fractures, femur fracture, and other unknown causes. Objectives: Spontaneus fractures caused by caregivers frequently occur without any noticeable trauma and at present, predicting the risk of occurrence is difficult. This study aimed to explore the usefulness of bone metabolism markers in predicting the risk for spontaneus fractures caused by caregivers. Methods: Study subjects were selected from a pool of 28 patients (3 men; 25 women) with 33 spontaneus fractures caused by caregivers who were treated in our hospital between April 2006 and July 2016. Patients were selected based on the following inclusion criteria: no renal dysfunction (eGFR ≥60) and those who had undergone measurement of bone metabolism markers. Finally, 12 women with a mean age at onset of 90.6 (76–100) years were enrolled in the study. The following markers were evaluated: the bone formation markers bone type alkaline phosphatase and intact procollagen type 1 amino-terminal propeptide; the bone resorption markers tartrate-resistant acid phosphatase (TRACP)-5b, urinary deoxypyridinoline (DPD), and serum N-telopeptide; and the bone quality markers undercarboxylated osteocalcin (ucOC), urinary pentosidine (Pen), and homocysteine (Hcy). Results: Low levels of bone metabolism markers were not observed in these subjects. However, TRACP-5b levels were high in six subjects while urinary DPD levels were abnormally high in all subjects with a mean value of 23.3 (9.2–41.4) nmol/mmol creatinine (Cr). With regards to bone quality markers, levels of Hcy and ucOC were high in two and three subjects, respectively; while Pen levels were abnormally high in ten subjects with a mean value of 0.183 (0.0774–0.3115) μg/mg Cr. Conclusions: The majority of subjects with spontaneus fractures caused by caregivers had untreated osteoporosis and some had repeated fractures, indicating that early treatment of osteoporosis is important. Assessing osteoporosis in bedridden patients is challenging as measurement of bone density is often difficult due to spinal deformity and contracture. Our results suggest that among the bone metabolism markers, DPD and Pen may be useful predictors for the risk of spontaneus fractures caused by caregivers. References: T Kashiwagura et al. Clinical results of spontaneous fractures in the bedridden patients unintentionally caused by caregivers. Orthop Surg Traumatol 56:189–193, 2013. Acknowledgements: The authors would like to thank Y. Sasaki for technical assistance. Disclosure of Interest: None declared